If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43 = 3u + 13 Reorder the terms: 43 = 13 + 3u Solving 43 = 13 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 43 + -3u = 13 + 3u + -3u Combine like terms: 3u + -3u = 0 43 + -3u = 13 + 0 43 + -3u = 13 Add '-43' to each side of the equation. 43 + -43 + -3u = 13 + -43 Combine like terms: 43 + -43 = 0 0 + -3u = 13 + -43 -3u = 13 + -43 Combine like terms: 13 + -43 = -30 -3u = -30 Divide each side by '-3'. u = 10 Simplifying u = 10
| 2(4t-6)=25t+7 | | x+4z=17 | | 5x+50=7x-14 | | 3b^2-4b+6=0 | | -2(6+m)=-16+2m | | 4.5-x=3.5-x | | 5(5x+10)-13x+64=198 | | x^3+16x^2+9x+27=0 | | 5(5x+10)-13x+64=194 | | 12x=4x-88 | | x+x^2=-.25 | | -4y+-5.6-4.4y= | | 9-2m=7+2(m-3) | | 3-[n-1]=-2 | | 3x+2y=1.6 | | 39-3n=-24n-18 | | 3=w+6 | | 15(m-3)+3m=45 | | 14-n=-2 | | (x+6)[x-(5-2i)][x-(5+2i)]=0 | | (3t/6u)^-4 | | -6x+-18=-6 | | 2x-y=-0.1 | | 3(4m-5)-2m=0 | | 8-3[8n]=-88 | | 329.99=25.75+23.50 | | n+35=-32 | | 19x-4(5x-8)=38 | | -5(x+-1)=10+-2x | | -3(x+-1)=10-2x | | 5.72x+16=32.7184+4x | | X/4-9-10 |